2018
DOI: 10.15252/embj.201899264
|View full text |Cite
|
Sign up to set email alerts
|

Substrate relay in an Hsp70‐cochaperone cascade safeguards tail‐anchored membrane protein targeting

Abstract: Membrane proteins are aggregation-prone in aqueous environments, and their biogenesis poses acute challenges to cellular protein homeostasis. How the chaperone network effectively protects integral membrane proteins during their post-translational targeting is not well understood. Here, biochemical reconstitutions showed that the yeast cytosolic Hsp70 is responsible for capturing newly synthesized tail-anchored membrane proteins (TAs) in the soluble form. Moreover, direct interaction of Hsp70 with the cochaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(128 citation statements)
references
References 61 publications
8
120
0
Order By: Relevance
“…To test the effect of the SR MoRF deletion on SRP-dependent protein targeting, we measured the in vivo targeting and translocation of a model substrate, DHC-αF, in which the signal sequence of prepro-α-factor is replaced by the hydrophobic core of the dipeptidyl aminopeptidase B signal sequence to convert it into an SRP-dependent substrate protein (Fig. S2 D; Ng et al, 1996; Cho and Shan, 2018). DHC-αF was efficiently glycosylated upon insertion into the ER (Yabal et al, 2003; Wang et al, 2010; Rao et al, 2016), providing a quantitative readout for its targeting and translocation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the effect of the SR MoRF deletion on SRP-dependent protein targeting, we measured the in vivo targeting and translocation of a model substrate, DHC-αF, in which the signal sequence of prepro-α-factor is replaced by the hydrophobic core of the dipeptidyl aminopeptidase B signal sequence to convert it into an SRP-dependent substrate protein (Fig. S2 D; Ng et al, 1996; Cho and Shan, 2018). DHC-αF was efficiently glycosylated upon insertion into the ER (Yabal et al, 2003; Wang et al, 2010; Rao et al, 2016), providing a quantitative readout for its targeting and translocation.…”
Section: Resultsmentioning
confidence: 99%
“…DHC-αF was efficiently glycosylated upon insertion into the ER (Yabal et al, 2003; Wang et al, 2010; Rao et al, 2016), providing a quantitative readout for its targeting and translocation. To measure the targeting kinetics of newly synthesized proteins, we performed pulse-chase assays coupled to immunoprecipitation of HA-tagged substrate proteins (see Materials and methods; Cho and Shan, 2018). The results showed that, while DHC-αF was rapidly and nearly completely translocated in SRP101 cells, the translocation of DHC-αF was substantially delayed and plateaued at <50% in srp101 dM cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since not all ASNA-1 homologs have TAP-targeting activity (Farkas et al, 2019), it was important to examine whether C. elegans ASNA-1 has this function. In addition, parallel pathways like EMC, HSP70/HSC40, and SND participate in TAP targeting (Aviram et al, 2016; Casson et al, 2017; Cho and Shan, 2018; Guna et al, 2018). It was possible that compensated TAP targeting by these pathways would make it difficult to detect a targeting defect in asna-1 single mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, TA proteins represent 3–5% of the eukaryotic membrane proteome (Hegde and Keenan, ). It is well known that the targeting signal of TA proteins is embedded in their C‐terminal domain; however, in spite of a progress in understanding of the mechanisms involved in the sorting of TA proteins into ER (Mateja et al ., ; Cho and Shan, ), the targeting into the OMM, is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%